Islam Moderat Konteks Indonesia Dalam Perspektif History - Munawir Haris (LPPM IAIN Sorong, 2015)
Really grievous if difference in Islam, what basically leave from difference of understanding and interpretation of to text al-Qur’an and alHadits, result disharmony in going into society and state. Actually, along the length of the difference based on hotly values Ukhuwah Basyariah (brotherhood of between mankind), ukhuwah Islamiyah (brotherhood of between Islam people humanity), hablu minannaas (good rapport with fellow being), and ikhtilafu ummati rahmatun (difference is blessing), not generate problems. Specially in Indonesia, from fact available for seen, seems not yet show that the difference of blessing. Thereby, this article invite to try to refer back history, what comprehending Islam and ber-Islam which ought to be applied in Indonesia context so that Indonesia man in understanding be not trapped into abundant ekstrimitity. Concepted moderating Islam, basically only limited to bargain which solely wishing assist public in general in comprehending Islam. Act moderate in berIslam is not an things digressing in Islam teaching, because this thing is detectable of the reference, is good in al-Qur’an, al-Hadits, and also behavior of man in history. Develop understanding “Moderating Islam” for Indonesia context it can be assumed so important. Isn’t it true known that in this region there are understanding in Islam, immeasurable of religion, and multi-etnis. Concepted moderating Islam invite, what Islam is comprehended in kontekstual, comprehend that variance and difference is sunnatullah, have no refused by the existence. If this thing was practiced, it can be believed by Islam will become blessing religion for universe.